Trematodes parasiting in giant lizards in Vietnam - Doanh, Pham Ngoc; Le, Nguyen Thi (Academia Journal of Biology, 2015)
Two giant lizard species Varanus nebulosus (Gray, 1831) and Varanus salvator (Laurentin, 1786) were examined for parasites. In this paper, the authors report the trematoda infection rate and describe 8 species of trematodes collected from these studied giant lizards. The infection rate in Varanus nebulosus is at 73.6% (14/19) and 85% Varanus salvator are infected. Eight species of trematodes from giant lizards are identified as Singhiatrema vietnamensis Curran  S. S., Overstreet R. M., The D. T., Le. N. T., 2001, Testisacculus indicus (Bhalerao, 1931), Haplorchis pumilio (Loos, 1896), Diplodiscus mehrai Pande, 1937, Encyclometra colubrimurorum (Rud., 1819), Euparadistomum varani Tubangui, 1931, Mesocoelium pearsei Goto et Ozaki, 1930 and Meristocotyle sp. The last species may be a new species for science.